A large national survey of public perceptions of CCS technology in China. (15th November 2015) - Chen, Zheng-Ao; Li, Qi; Liu, Lan-Cui; Zhang, Xian; Kuang, Liping; Jia, Li; Liu, Guizhen
Highlights: First national survey of public perceptions of CCS technology in China. Comprehensive analysis on Chinese public understanding and concerns on CCS. High-level suggestions in raising social acceptance of CCS technology in China. Abstract: The success of a new technology (like carbon capture and storage (CCS)) not only depends on sound technical and engineering practice but also involves societal, political and economic factors. High public acceptance is viewed as one of the critical factors. To date, there has been little systematic research into public communication and engagement in regard to CCS in China. A national survey on public perception (but biased towards the views of the educated elite of the Chinese population) of CCS technology was conducted from July 2013 to December 2013. The objectives of the survey were to assess the following issues: public understanding of the climate sciences, society's knowledge and acceptance of low emission technologies (especially of CCS technology), public interests and concerns about the positive and negative impacts of CCS technology, and public attitudes towards CCS policies supported by the government. Finally, high-level suggestions for mechanisms to raise public understanding and frame the social acceptance on CCS technology in China are proposed based on a SWOT analysis.